Mapping of quantitative trait loci associated with reproductive-stage salt tolerance in rice - Hossain, H.; Rahman, M.A.; Alam, M.S.; Singh, R.K. (Wiley, 2015)
Salinity tolerance in rice varies with the state of growth, with the seedling and reproductive stages being the most sensitive. However, association between tolerances at the two stages is poor, suggesting that they are regulated by different processes and genes. Tolerance at the reproductive stage is the most crucial as it determines grain yield. An F2 mapping population was developed from two rice genotypes contrasting in tolerance: Cheriviruppu and Pusa Basmati 1 (PB1). Cheriviruppu is highly tolerant at the reproductive stage, while PB1 is highly sensitive at both seedling and reproductive stages. One hundred and thirty‐one microsatellite markers polymorphic between the parents were used to construct a linkage map of 1458.5 cM (Kosambi), with a mean intermarker distance of 11.1 cM. Sixteen QTLs with LOD values ranging from 3.2 to 22.3 were identified on chromosomes 1, 7, 8 and 10, explaining 4–47 % of the phenotypic variation. The maximum number of QTL clusters for different component traits was colocalized on the long arm of chromosome 1 and chromosome 7. We identified several significant epistatic interactions, including three inter‐QTL interactions, using MapManager. The results suggest that pollen fertility, Na+ concentration and Na/K ratio in the flag leaf are the most important mechanisms controlling salt tolerance at the reproductive stage in rice. The study reports the construction of a genetic map for reproductive‐stage salt tolerance in rice and demonstrates its utility for molecular mapping of QTLs controlling salinity tolerance‐related traits, which will be useful in marker‐assisted selection in the future.